Digital Library Management: a Worthy and Well-timed Makeover for the Information Professional - Ongus, Raymond Wafula; Kemparaju, T. D.; Nyamboga, Constantine Matoke; Veerabasavaiah, M. (Journal of Information and Knowledge, 2008)
This paper examines digital libraries principally from the management perspective. For the purpose of appreciating the intrinsic concepts involved, it starts with a comprehensive discussion of definitions, followed by basic principles pertaining to digital libraries. Next, it gives a glimpse into a wide-ranging spectrum of reasons as to why digital libraries are mushrooming predominantly in the developed world and in some developing countries as well. Reasons for the management of these types of libraries are also brought into view. Core competencies expected of digital librarians are outlined, in the wake of the new and continuously dynamic technological dispensation. The paper stresses the need for a paradigm shift in information management strategies in as far as digital libraries are concerned. This is considered to be crucial if at all information professionals are to gain maximum mileage in their noble mission of satisfying evolving user needs. Urgent attention ought to be directed towards managing of digital libraries, as a means of enabling contemporary information professionals to assert their unique role in society, not only as information gatekeepers but as information gateways, as well.